(untitled) (International Journal of Physiotherapy, 2016)
Background: Piriformis syndrome is a commonly overlooked specific cause of low back pain. Apart from mimicking the sciatica-like symptoms, unilateral piriformis tightness can cause rotational dysfunction and pain in the lumbar region. This could lead to low back pain which is a common musculo skeletal problem and a major reason for activity limitation. Stretching the piriformis tightened muscle is a preferred choice of treatment against surgical intervention to release the muscle. Mulligan’s mobilization is based on movement with mobilization which is proven to be effective in many musculo skeletal dysfunctions including the lumbar spine. The purpose of this study is to explore and compare the two treatment methods in relieving the low back pain in clinical conditions with piriformis syndrome. Methods: In this experimental study, 40 patients with piriformis syndrome were selected and divided into two groups. One group was given only piriformis stretching for the tightened muscle and the other group given Mulligan mobilization for lumbo sacral joints. VAS and lower limb functional index were taken to compare before and after the treatment regime of 4 weeks. Results: There was no significant difference between the two groups in both pain scale and lower limb mobility and function. But there was significant improvement in pain relief and LLFI after the treatment regime in both groups compared to the pre-treatment status. Conclusion: Even as the piriformis syndrome is caused by the tightness of the muscle, the consequence in the lower back and lumbar spine mobility can be improved by a Mulligan mobilization as a single mode of intervention .